2016
DOI: 10.2967/jnumed.116.176511
|View full text |Cite
|
Sign up to set email alerts
|

Posttreatment PET/CT Rather Than Interim PET/CT Using Deauville Criteria Predicts Outcome in Pediatric Hodgkin Lymphoma: A Prospective Study Comparing PET/CT with Conventional Imaging

Abstract: Data about the significance of F-FDG PET at interim assessment and end of treatment in pediatric Hodgkin lymphoma (HL) are limited. Patients (≤18 y) with HL were prospectively evaluated with contrast-enhanced CT (CECT) and PET combined with low-dose CT (PET/CT) at baseline, after 2 cycles of chemotherapy, and after completion of treatment. Revised International Working Group (RIW) criteria and Deauville 5 point-scale for response assessment by PET/CT were used. All patients received doxorubicin (Adriamycin), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 21 publications
2
19
0
1
Order By: Relevance
“…Among patients who received radiotherapy, PET-negative patients also showed a longer TTP than PET-positive patients, although they received a higher dose of radiotherapy. These results are similar to those of the studies discussed above [11,12] in which both early and late therapy response assessment with 18 F-FDG PET were able to identify paediatric HL patients with longer survival. Comparing the calculated predictive values for all three PET scans (i.e.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Among patients who received radiotherapy, PET-negative patients also showed a longer TTP than PET-positive patients, although they received a higher dose of radiotherapy. These results are similar to those of the studies discussed above [11,12] in which both early and late therapy response assessment with 18 F-FDG PET were able to identify paediatric HL patients with longer survival. Comparing the calculated predictive values for all three PET scans (i.e.…”
Section: Discussionsupporting
confidence: 89%
“…This difference was also seen between patients with PR in the range 50-75% and those with a response of ≥75%. Furthermore, Bakhshi et al [12], in a recent study evaluating the role of interim FDG PET after two cycles of chemotherapy in a paediatric HL cohort, found that interim PET/CT had a significantly higher specificity than conventional imaging. However, they did not recommend treatment reduction based on the interim PET/CT assessment by either the Revised International Working Group criteria or the Deauville score, as few patients would have benefited from less intense therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have confirmed that the DS, where values of 1–3 are defined as negative results and 4–5 are defined as positive results on I-PET/CT, can better predict PFS and OS, with good concordance among reviewers and inter-reader reliability in HL and NHL [ 40 42 ]. Jiang et al [ 25 ] evaluated the prognostic value of I-PET/CT using the DS and found that NPVs were better than PPVs in predicting PFS and OS, with NPVs of 87.5% and 96.9%, respectively, and PPVs of 60.7% and 39.3%, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…In other studies on the value of interim FDG-PET/CT in patients with advanced-stage Hodgkin lymphoma treated with ABVD, the predictive value was less strong, with PFS rates ranging between 28.8% and 43% for those with positive interim FDG-PET/CT results [6][7][8]. Of note, in two recent studies including an ABVD treated cohort of early-and advanced-stage Hodgkin lymphoma patients, interim FDG-PET/CT had minor or no predictive value at all, with interim FDG-PET/CT positive patients having PFS of 56.3% [9] and 100% [10], respectively. In patients treated with BEACOPP, the prognostic value of interim FDG-PET/CT diminishes drastically.…”
Section: Fundingmentioning
confidence: 98%